Effects of Galactic Environment on Size and Dark Matter Content in Low-mass Galaxies - Francisco J. Mercado; Jorge Moreno; Robert Feldmann; Marckie Zeender; José A. Benavides; Joanna M. Piotrowska; Courtney Klein; Coral Wheeler; Lina Necib; James S. Bullock; Philip F. Hopkins (The Astrophysical Journal)
We utilize the cosmological volume simulation FIREbox to investigate how a galaxy’s environment influences its size and dark matter content. Our study focuses on approximately 1200 galaxies (886 central and 332 satellite halos) in the low-mass regime, with stellar masses between 10 ^6 and 10 ^9 M _⊙ . We analyze the size–mass relation ( r _50 – M _⋆ ), the inner dark matter mass–stellar mass ( ${M}_{{\rm{DM}}}^{50}$ – M _⋆ ) relation, and the halo mass–stellar mass ( M _halo – M _⋆ ) relation. At fixed stellar mass, we find that galaxies experiencing stronger tidal influences, indicated by higher Perturbation Indices (PI > 1) are generally larger and have lower halo masses relative to their counterparts with lower Perturbation Indices (PI < 1). Applying a Random Forest regression model, we show that both the environment (PI) and halo mass ( M _halo ) are significant predictors of a galaxy’s relative size and dark matter content. Notably, because M _halo is also strongly affected by the environment, our findings indicate that environmental conditions not only influence galactic sizes and relative inner dark matter content directly, but also indirectly, through their impact on halo mass. Our results highlight a critical interplay between environmental factors and halo mass in shaping galaxy properties, affirming the environment as a fundamental driver in galaxy formation and evolution.